2016
DOI: 10.1097/qai.0000000000000765
|View full text |Cite
|
Sign up to set email alerts
|

Participant Experiences and Views of Odor and PrePex Device Removal Pain in a VMMC Pilot Study in Botswana

Abstract: Objective:To assess participant experiences and perceptions of removal pain and odor associated with the PrePex device procedure.Methods:We analyzed data from a PrePex device pilot implementation study of 802 male participants aged 18–49 years at 2 clinics in Botswana, 2013. Study staff administered survey questions on device-related odor and assessed pain using visual analog scale scores categorized as no pain (0), mild (1–4), moderate (5–7), or severe pain (8–10).Results:Mean participant age was 27.7 (range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…However, device removal was associated with moderate to severe pain that abated within half an hour[ 13 ]. Other studies have also reported on moderate and severe pain experienced during device removal for example: in Zimbabwe 28% of participants experienced mild to moderate pain during removal [ 21 ], in Botswana 6% and 2% had moderate to severe pain respectively [ 22 ], and in Mozambique 38% reported severe or unbearable pain and 22% had moderate pain during removal [ 18 ]. Although the manufacturer did not recommend analgesia for placement or removal, our findings indicate that providing analgesia prior to PrePex device removal reduced the proportion of participants reporting severe pain compared to no analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…However, device removal was associated with moderate to severe pain that abated within half an hour[ 13 ]. Other studies have also reported on moderate and severe pain experienced during device removal for example: in Zimbabwe 28% of participants experienced mild to moderate pain during removal [ 21 ], in Botswana 6% and 2% had moderate to severe pain respectively [ 22 ], and in Mozambique 38% reported severe or unbearable pain and 22% had moderate pain during removal [ 18 ]. Although the manufacturer did not recommend analgesia for placement or removal, our findings indicate that providing analgesia prior to PrePex device removal reduced the proportion of participants reporting severe pain compared to no analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…Introduction studies of PrePex in adults in Malawi, Zambia, Zimbabwe, Mozambique, South Africa, and Botswana confirm that the device is safe, including in the context of routine service delivery by nurses, and that clients are satisfied and would recommend it to their peers. 14 19 A study of PrePex in Zimbabwean adolescents aged 13–17 years provides the first safety data in this important younger age group, constituting the largest number of clients who have sought VMMC services thus far. 20 Although a greater proportion of adolescents versus adults are anatomically ineligible for PrePex, adverse event rates, perceptions of pain, and healing time are all less than observed using PrePex in adults.…”
Section: Safetymentioning
confidence: 99%
“…This supplement contains 16 articles from 8 countries examining different aspects of the introduction of devices into VMMC and focus on the following: Safety and acceptability of device introduction in Botswana, South Africa, Malawi, Zambia, Zimbabwe, Mozambique, and Kenya 14 20 , 22 24 The WHO-defined pathway for the evaluation of devices for VMMC programs for HIV prevention 13 Estimated unit costs of device-based VMMC and cost of device introduction 27 , 28 Impact of devices on demand for VMMC services 26 Provider training and client education. 21 , 25 …”
Section: Safetymentioning
confidence: 99%
See 2 more Smart Citations